Evaluating Swine Injection Technologies as a Workplace Musculoskeletal Injury Intervention: A Study Protocol. (29th October 2017) - Trask, Catherine; Bath, Brenna; Milosavljevic, Stephan; Kociolek, Aaron M.; Predicala, Bernardo; Penz, Erika; Adebayo, Olugbenga; Whittington, Lee
Abstract : Intensification of modern swine production has led to many new technologies, including needleless injectors. Although needleless injectors may increase productivity (by reducing injection time) and reduce needlestick injuries, the effect on risk for musculoskeletal disorders is not clear. This project will compare conventional needles with needleless injectors in terms of cost, productivity, injury rates, biomechanical exposures, and worker preference. Muscle activity (EMG) and hand/wrist posture will be measured on swine workers performing injection tasks with both injection methods. Video recordings during the exposure assessments will compare the duration and productivity for each injection method using time-and-motion methods. Injury claim data from up to 60 pig barns will be analyzed for needlestick and musculoskeletal injuries before/after needleless injector adoption. Workers and managers will be asked about what they like and dislike about each method and what helps and hinders successful implementation. The information above will be input into a cost-benefit model to determine the incremental effects of needleless injectors in terms of occupational health, worker preference, and the financial "bottom line" of the farm. Findings will be relevant to the swine industry and are intended to be transferable to other new technologies in animal production.